Adjuvant chemotherapy for patients with gastric neuroendocrine carcinomas or mixed adenoneuroendocrine carcinomas. Issue 9 (23rd April 2020) - Lin, J-P; Zhao, Y-J; He, Q-L; Hao, H-K; Tian, Y-T; Zou, B-B; Jiang, L-X; Lin, W; Zhou, Y B; Li, Z; Xu, Y-C; Zhao, G; et al.
Abstract: Background: The aim of this study was to evaluate whether adjuvant chemotherapy is associated with improved survival in patients with resectable gastric neuroendocrine carcinomas (G-NECs) or mixed adenoneuroendocrine carcinomas (G-MANECs). Methods: The study included patients with G-NECs or G-MANECs who underwent surgery in one of 21 centres in China between 2004 and 2016. Propensity score matching analysis was used to reduce selection bias, and overall survival (OS) in different treatment groups was estimated by the Kaplan–Meier method. Results: In total, 804 patients with resectable G-NECs or G-MANECs were included, of whom 490 (60·9 per cent) received adjuvant chemotherapy. After propensity score matching, OS in the chemotherapy group was similar to that in the no-chemotherapy group. Among patients with G-NECs, survival in the fluorouracil (5-FU)-based chemotherapy group and the non-5-FU-based chemotherapy group was similar to that in the no-chemotherapy group. Similarly, etoposide plus cisplatin or irinotecan plus cisplatin was not associated with better OS in patients with G-NECs. Among patients with G-MANECs, OS in the non-5-FU-based chemotherapy group was worse than that in the no-chemotherapy group. Patients with G-MANECs did not have better OS when platinum-based chemotherapy was used. Conclusion: There was no survival benefit in patients who received adjuvant chemotherapy for G-NECs or G-MANECs. Graphical Abstract: This multicentre study enrolled 804 patients with resectable gastric neuroendocrine carcinomas and gastric mixed adenoneuroendocrine carcinomas. In propensity score matching analysis, there were no associations between the use of adjuvant chemotherapy and improved overall survival. Similar results were obtained in stratified analysis according to different chemotherapy regimens. No benefit